FAKTOR-FAKTOR YANG MEMENGARUHI CASH HOLDING PADA PERUSAHAAN PUBLIK DAN PERUSAHAAN MILIK PEMERINTAH: TINJAUAN PUSTAKA - Adli Rikanda Saputra (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
Corporate cash holding is a strategic financial decision that reflects a firm’s ability to maintain liquidity, respond to uncertainty, and support investment opportunities. This study aims to synthesize previous research on the factors influencing cash holding in public companies. Particular attention is given to government-owned companies. This research applies a literature review method by examining relevant studies from major academic databases and analyzing them through thematic synthesis. The review identifies that corporate cash holding decisions are shaped by firm-specific, governance-related, macroeconomic, and institutional factors. These factors interact in complex ways and influence both the level and value of corporate cash holding. The main determinants found in the literature include firm size, leverage, cash flow, cash flow volatility, growth opportunities, net working capital, corporate governance, board characteristics, ownership structure, political connections, financial constraints, dividend policy, CEO characteristics, ESG performance, and digital finance. In government-owned companies, state ownership, political connections, governance quality, and institutional environment are particularly important because these factors may influence both the level and value of cash holding. The findings also show that no single theory fully explains cash holding behavior, as trade-off theory, pecking order theory, agency theory, and free cash flow hypothesis each provide partial explanations. This study concludes that future research should adopt more comparative, longitudinal, and context-sensitive approaches, particularly in examining cash holding in government-owned companies amid digital transformation, sustainability pressures, and increasing economic uncertainty.